Analisis System Thinking pada Pembelajaran Matematika dengan Menggunakan Model Pembelajaran Problem Based Learning untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa - Florenza, Florenza; Casnan, Casnan (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to analyze the influence of the Problem Based Learning learning model and determine the improvement of students' mathematical problem-solving skills. This study uses a mix method with an exploratory sequential design or also known as a three-phase design. This research was carried out at SMPN 2 Tirtajaya in May 2024. The samples taken consisted of class VII-A, Experimental class, and class VII-D, Control class. The number of each class consists of 40 students. This study uses System Thinking to see and analyze problems in mathematics learning. Non-parametric analysis technique is the mann-whitney test through SPSS software. The results of the analysis show that the main problems in mathematics learning are learning methods, student activity, study groups and case studies that are suitable for daily life, this is in accordance with the characteristics of Problem Based Learning that can be implemented in the learning process. The application of Problem Based Learning in mathematics learning shows that there is a significant difference between students' mathematical problem-solving ability after applying the Porblem-based Learning learning model in the experimental class and the conventional model in the control class